Kepemimpinan Transformasional dalam Proses Penerimaan dan Proses Seleksi Pemimpin Publik dalam Menciptakan Kepercayaan di Indonesia - Irwan Zulkifli (Binus Business Review, 2013)
Leaders are highly influential figure to public. Currently, public expect a leader who is really competent and ethical, and has the ability to carry out the mandates. Many leaders are not trusted; it could be because the process of selecting leaders regarded deviant and did not meet expectations, and even (s)he is nowalready a leader, her/his ability is far from expectations. People have been very bored with always be the same leadership style from period to period. Currently, it is required leaders who prioritize the public interests than the personal or group interests. Therefore, it is necessary to bring about the style of leadership expected by the public, especially for public leaders. So that, the public involvement in the process of selection of leaders is essential. Recruitement of leaders from industry is very expected, that leader competencies are better and adaptable in business environment. Thus it may improve the national economic competitiveness to global competition.